2021
DOI: 10.1111/dom.14581
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of insulin therapy and insulin daily doses in children and adolescents with type 1 diabetes in Germany

Abstract: Aim To describe the different insulin therapy patterns and insulin daily doses in children and adolescents (aged 1‐17 years) with type 1 diabetes. Methods This cross‐sectional study based on the longitudinal prescription (LRx) database (IQVIA) included children and adolescents who received at least two insulin prescriptions of the same drug from 1 January 2016 to 31 December 2019. The study outcomes included the proportion of patients with insulin pumps and multiple daily injection therapy, human insulin and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Similar results in the literature showed a positive correlation between the total daily insulin intake and ganglion cell complex thickness [ 25 ]. A high total daily insulin intake is a surrogate for intensive treatment, linked to a long-term beneficial effect on vascular damage [ 26 , 27 , 28 ]. Regarding the glycemic control analysis through the HbA1c and MAGE assessment, it is essential to remember that these parameters only reflect the last few days to months of the glucose balance.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results in the literature showed a positive correlation between the total daily insulin intake and ganglion cell complex thickness [ 25 ]. A high total daily insulin intake is a surrogate for intensive treatment, linked to a long-term beneficial effect on vascular damage [ 26 , 27 , 28 ]. Regarding the glycemic control analysis through the HbA1c and MAGE assessment, it is essential to remember that these parameters only reflect the last few days to months of the glucose balance.…”
Section: Discussionmentioning
confidence: 99%
“…The use of nonpharmacological measures has increased to reduce pain. (25,26) The non-pharmacological measures such as shot blocker and buzzy bee are safer than pharmacological measures and have fewer or no side effects. Shot blocker includes a number of short, blunt skin contact points on its underside and a centrally located opening through which injections are administered.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the daily dose of insulin needed for each person can vary greatly, depending on body weight and insulin sensitivity. 71 -74 Over the past 35 years, technological innovations have enabled the design of accurate pen injectors with small, single-use needles and low manual injection force to improve the overall injection experience for individuals, 75 with improved accuracy and reproducibility of the delivery of insulin doses, including small doses, compared with vial and syringe. 76 -79 Asakura et al 36 reported that using a pen injector was more accurate than vial and syringe regardless of HCP experience in insulin therapy.…”
Section: Factors Affecting the Performance Of Insulin Pen Injector Te...mentioning
confidence: 99%